Characterization and regulation of the 3beta-hydroxysteroid dehydrogenase isomerase enzyme in the rat sciatic nerve - Coirini, Hector (2003)
In the peripheral nervous system, progesterone (PROG) has a stimulatory effect on myelination. It could be derived from local synthesis, as Schwann cells in culture express the 3beta-hydroxysteroid dehydrogenase (3beta-HSD) and convert pregnenolone (PREG) to PROG. Although 3beta-HSD mRNA can be detected by RT-PCR in peripheral nerves, the activity of the enzyme has so far not been demonstrated and characterized in nerve tissue. In this study, we show that homogenates prepared from rat sciatic nerves contain a functional 3beta-HSD enzyme and we have analysed its kinetic properties and its regulation by steroids. The activity of 3beta-HSD in homogenates was evaluated using 3H-labelled PREG as a substrate and NAD+ as a cofactor, the levels of steroids formed were calculated either by extrapolating the relationship between tritiated peaks obtained by TLC to the initial amount of PREG, or by gas chromatography/mass spectrometry determination. A rapid increase in PROG formation was found between 0 and 50 min of incubation and no further significant changes were observed between 1 and 4 h. The calculated Km value (1.06 +/- 0.19 microm) was close to the values described for the 3beta-HSD type-I and type-IV isoforms. Trilostane, a competitive inhibitor of the 3beta-HSD caused a potent inhibition of the rate of conversion of PREG to PROG (IC50 = 4.06 +/- 2.58 microm). When the effects of different steroids were tested, both oestradiol and PROG significantly inhibited the conversion of PREG to PROG.